Low carbohydrate diet prevents Mcl-1-mediated resistance to BH3-mimetics - Rubio-Patiño, Camila (Oncotarget, 2016)
Overexpression of Mcl-1 is implicated in resistance of several cancers to chemotherapeutic treatment, therefore identifying a safe way to decrease its expression in tumor cells represents a central goal. We investigated if a modulation of the diet could impact on Mcl-1 expression using a Myc-driven lymphoma model. We established that a partial reduction of caloric intake by 25% represents an efficient way to decrease Mcl-1 expression in tumor cells. Furthermore, using isocaloric custom diets, we observed that carbohydrates (CHO) are the main regulators of Mcl-1 expression within the food. Indeed, feeding lymphoma-bearing mice with a diet having 25% less carbohydrates was sufficient to decrease Mcl-1 expression by 50% in lymphoma cells. We showed that a low CHO diet resulted in AMPK activation and mTOR inhibition leading to eukaryotic elongation factor 2 (eEF2) inhibition, blocking protein translation elongation. Strikingly, a low CHO diet was sufficient to sensitize Myc-driven lymphoma-bearing mice to ABT-737-induced cell death in vivo. Thus reducing carbohydrate intake may represent a safe way to decrease Mcl-1 expression and to sensitize tumor cells to anti-cancer therapeutics.